Guinea : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1999)
This paper reviews economic developments in Guinea during 1990-98. Economic developments were dominated by the coming on stream of important oil fields in 1992 and 1996, and the subsequent breakdown in fiscal discipline and transparency. In response to the January 1994 devaluation of the CFA franc, there was also an upturn in the non-oil sector, led by intensification in logging activity that resulted in an unsustainable level of timber output in 1997. Real GDP growth averaged 8.5 percent a year in 1992-95, and rose to 29 percent in 1996.